2018
DOI: 10.3390/catal8110486
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ricinoleic Acid Preparation Using Lipozyme TLIM as a Novel Biocatalyst: Optimized by Response Surface Methodology

Abstract: Ricinoleic acid (RA) is an important raw material for plasticizers, emulsifiers, and nanomaterials. In this work, a green and efficient method was developed for RA production. Results showed that Lipozyme TLIM can be used as a novel biocatalyst to catalyze the hydrolysis of castor oil (CO) for RA preparation. Response surface methodology (RSM) was used to evaluate and optimize the effects of reaction variables on the hydrolysis of CO. Reaction conditions were optimized as follows: 41.3 °C, enzyme load 8.9%, 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Consequently, mild enzymatic synthesis has been described as a plausible alternative, and some enzymes such as Avena sativa L., Rizopus oryzae lipase, Pseudomonas aeruginosa KKA-5 lipase, or Thermomyces lanuginose, among others, have been used. 125 , 126 …”
Section: Modifications Of Vegetal Oils To Improve Oxidative Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, mild enzymatic synthesis has been described as a plausible alternative, and some enzymes such as Avena sativa L., Rizopus oryzae lipase, Pseudomonas aeruginosa KKA-5 lipase, or Thermomyces lanuginose, among others, have been used. 125 , 126 …”
Section: Modifications Of Vegetal Oils To Improve Oxidative Stabilitymentioning
confidence: 99%
“…Consequently, mild enzymatic synthesis has been described as a plausible alternative, and some enzymes such as Avena sativa L., Rizopus oryzae lipase, Pseudomonas aeruginosa KKA-5 lipase, or Thermomyces lanuginose, among others, have been used. 125,126 Natural estolides have been reported to occur in plants that produce hydroxy FAs such as ricinoleoyl estolides from castor oil or TAG estolides in several plant genus like Physaria, Heliophila amplexicaulis, Lesquerella, Nerium, Sapium sebiferum, Trewia nudiflora, and Avena sativa. The best known of the hydroxy acids of the seeds of some of these plants are those found in lesquerella oil in which 55%−60% corresponds to the hydroxy FA lesquerolic (14-hydroxy-cis-11-eicosenoic acid) and 2%−4% to the auricolic acid (14-hydroxy-cis-11-cis-17eicosenoic acid) and the ricinoleic acid D-(−)12-hydroxyoctadec-cis-9-enoic acid) which comprises up to 90% of castor oil (from Ricinus communis).…”
Section: ■ Stabilization Of Vegetal Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies regarding enzyme hydrolysis have investigated a wide variety of raw materials [38][39][40], applying commercial emulsifying agents (gum Arabic) and buffer solutions that lead to difficult and expensive recovery and purification of fatty acids. Thus, to overcome these drawbacks, recent studies have reported the production of fatty acids by enzymatic hydrolysis without the use of emulsifiers and buffer solutions [41][42][43]. Since the production of fatty acids from vegetable oils via lipase-catalyzed hydrolysis is well known, and the physicochemical properties of Moringa oleifera Lam seed oil have been well established [10], the development of a novel method to obtain fatty acid concentrates from Moringa oleifera Lam oil in a medium without the addition of buffer solutions or emulsifiers is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Novozym 435 is the general name for effective commercial enzymatic catalyst consisting of immobilized Candida antarctica lipase B on macroporous resin material, produced through submerged fermentation of a genetically modified Aspergillus niger (185). In several research works, Novozym-catalyzed transesterification was compared with other commercial lipases such as Amberlyst 15 (186), Lipozyme TL IM (187), Lipozyme TLIM (188), and other enzymatic catalysts and lipase mixtures (134).…”
Section: Enzyme Immobilizationmentioning
confidence: 99%